2020
DOI: 10.1007/s12520-020-01046-w
|View full text |Cite
|
Sign up to set email alerts
|

A cross-population study of sexual dimorphism in the bony labyrinth

Abstract: Previous research found sexual dimorphism in the bony labyrinth of a Greek population sample (Osipov et al. 2013). This study intends to investigate the nature of this structure’s sexual dimorphism across populations of diverse geographic origin and to identify the effect of inter-population variation on the accuracy of determining sex using the bony labyrinth. Three population samples of known sex were analyzed originating from Europe (n = 30), Africa (n = 38), and North America (n = 30). The discriminant fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Yet, this traditional osteometric method makes it difficult to isolate size and to differentiate shape variables which depend directly on size (allometry) from those that are function of other factors such as sex. The sexual dimorphism highlighted in the present study possibly reflects the differences of size and body mass that exist between males and females [29,34,44], which vary among human populations [41,43], more than pure shape differences by sex. To further explore modalities of sexual dimorphism of the bony labyrinth using a geometric morphometric approach could be valuable.…”
Section: Understanding Sexual Dimorphism Of Bony Labyrinth In Size and Shapementioning
confidence: 76%
See 2 more Smart Citations
“…Yet, this traditional osteometric method makes it difficult to isolate size and to differentiate shape variables which depend directly on size (allometry) from those that are function of other factors such as sex. The sexual dimorphism highlighted in the present study possibly reflects the differences of size and body mass that exist between males and females [29,34,44], which vary among human populations [41,43], more than pure shape differences by sex. To further explore modalities of sexual dimorphism of the bony labyrinth using a geometric morphometric approach could be valuable.…”
Section: Understanding Sexual Dimorphism Of Bony Labyrinth In Size and Shapementioning
confidence: 76%
“…European populations (continental vs. insular) [41,43]. Yet, comparisons are somewhat restricted because of differences in measurement sets and acquisition protocols (Table 7).…”
Section: Sexual Dimorphism Of the Bony Labyrinthmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups were scanned at several resolutions with several X-ray CT scanners across numerous institutions (Baab et al, 2018;Copes, 2012;Uhl et al, 2016Uhl et al, , 2020Ward et al, 2020). Scan resolution for these data is available in Table 3.…”
Section: Data Acquisition and Formattingmentioning
confidence: 99%
“…This equation was applied by Uhl et al (2016), but recent work shows that the equation does not work on all groups and again calls the existence of labyrinthine sexual dimorphism into question (Ward et al, 2020). Uhl et al (2020) reported that the levels of sexual dimorphism and bony labyrinth morphology differed across diverse population samples.…”
Section: Introductionmentioning
confidence: 99%